2008
DOI: 10.3892/or.19.4.1007
|View full text |Cite
|
Sign up to set email alerts
|

Activation of matrix metalloproteinase-9 by TNF-α in human urinary bladder cancer HT1376 cells: The role of MAP kinase signaling pathways

Abstract: Abstract. The expression of matrix metalloproteinase-9 (MMP-9) has been implicated in tumor invasion and metastasis. In this study, the factors and signaling pathways that are involved in the regulation of the MMP-9 expression were examined in urinary bladder cancer HT1376 cells. Tumor necrosis factor-α (TNF-α) stimulated the secretion of MMP-9 in HT1376 cells, as shown by zymography and immunoblot analysis. At the level of transcription, TNF-α also stimulated 5'-flanking promoter activity of MMP-9. Transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 23 publications
2
34
0
Order By: Relevance
“…56 Among the transcription factors that were studied at promoter pull-down analysis with the nuclear extract from murine sham and PBOO BSM tissues, transcription factor Ets-2 is overexpressed in human bladder cancer, 57 and SP-1 regulates tumor necrosis factor-␣-induced MMP-9 expression through ERK1/2 and p38 MAP kinase in bladder cancer cells. 58 However, in murine and human obstructed BSM tissues, Ets-2 and SP-1 are not overexpressed. Moreover, E2F and Sp-1 did not interact with murine CAV1 promoter as revealed at promoter pulldown analysis.…”
Section: Discussionmentioning
confidence: 99%
“…56 Among the transcription factors that were studied at promoter pull-down analysis with the nuclear extract from murine sham and PBOO BSM tissues, transcription factor Ets-2 is overexpressed in human bladder cancer, 57 and SP-1 regulates tumor necrosis factor-␣-induced MMP-9 expression through ERK1/2 and p38 MAP kinase in bladder cancer cells. 58 However, in murine and human obstructed BSM tissues, Ets-2 and SP-1 are not overexpressed. Moreover, E2F and Sp-1 did not interact with murine CAV1 promoter as revealed at promoter pulldown analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we focused on the regulatory roles of MMP-9 in IL-20-treated bladder cancer cells. The MMP-9 gene promoter contains several transcription factors, including NF-B, Sp-1, and AP-1 that are verified as binding sites in humans and mice (7)(8)(9)(10)(11)27). We first examined whether IL-20 can induce the activation of NF-B, Sp-1, and AP-1 in bladder cancer cells.…”
Section: Il-20 Activated Nf-b and Ap-1 Transcription Factors In Bladdmentioning
confidence: 99%
“…Previous studies have shown that MMP-9 supports crucial roles in the progression of bladder tumor in vitro and in vivo (4). Many studies have shown that growth factors and cytokines can stimulate MMP-9 expression in several types of cells (7)(8)(9)(10). Further studies have demonstrated that the transcription factors NF-B, Sp-1, and AP-1 are key transcriptional regulators responsible for the induction of MMP-9 in cancer cells (7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…Previous studies have indicated that TNF-α is a potent activator of MMP-9 in bladder cancer cells (Lee et al, 2008a(Lee et al, , 2008bShin et al, 2000). TNF-α induces MMP-9 expression in several tumor cell types by activation of the transcription factors NF-κB and AP-1 (Bond et al, 1998;Lee et al, 2008aLee et al, , 2008b.…”
Section: Introductionmentioning
confidence: 99%
“…However, based on previous reports, it is clear that several classes of proteins are involved in determining bladder cancer risk (Sier et al, 2000). Many studies have shown that MMP-9 is associated with invasiveness and bladder cancer progression (Davies et al, 1993;Lee et al, 2008aLee et al, , 2008bNutt et al, 2003;Shin et al, 2000).…”
Section: Introductionmentioning
confidence: 99%